A high dynamic range analog-front-end IC for electrochemical amperometric and voltammetric sensors. Issue 8 (August 2015) - Liu, Yun-Tao; Chen, Min; Li, Zhi-Chao; Wang, Ying; Chen, Jie
Abstract A wide input range, compliant with electrochemical amperometric and voltammetric sensors analog-front-end (AFE) integrated circuit (IC) is proposed. The AFE employs current integrator (CI) and trans-impedance amplifier (TIA) to deal with the input current in the order of nA and μA separately, achieving the advantage of high dynamic range and high resolution. Input voltage is converted to current through a series of precise resistances, and detected by CI or TIA, which making the input voltage range is not limited by the power supply. An incremental sigma-delta ADC is employed to digitize the transferring signal, reducing the complexity and power dissipation. Compared to other alternatives, the AFE could handle current and voltage signals simultaneously, and input voltage range is not limited by power supply, showing high dynamic range and resolution. The AFE IC is fabricated in 0.18 μm 1P5M mixed-signal CMOS process, occupies an area of 3.2 mm×2 mm, the readout circuit has a dynamic range of 120 dB, consumes 4.2 mA.